Availability, strategies of procurement and use of lithic resources in La Payunia, south of Mendoza - Salgán, María Laura (Revista del Museo de Antropología, 2015)
The regional structure of lithic resources in La Payunia suggests that the availability of lithic raw material for manufacture of instruments is heterogeneous, with areas of high and low abundance of rocks. The aim of this study is to assess the impact of the regional structure of lithic resources on archaeological assemblages. The results support the expectative from areas of abundance of rocks: primary processing tasks occur in the sources, the common sizes of debitage sites are small and the intensity reduction is high. The local raw material is used for manufacturing unifacial tools as well as the edges of flakes. On the other hand in areas of scarce raw materials, transport of cores and large flakes is frequent. The intensity of the reduction of rock is low, and local and non-local resources are used both for manufacturing unifacial and bifacial tools. These trends brings the possibility to outline modes procurement and mobility range of local and non-local lithic resources. Home ranges of about 200 km for mobile societies that during the late Holocene occupied La Payunia can be postulated.